PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN HASIL BELAJAR PKn KELASIVSDN 115 PEKANBARU - Dessyana Dessyana; Mahmud Alpusari; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:This research aims to improve student learning outcomes inCivics subjects (PKn) through the implementation of cooperative learning model Type Student Team Achievement Divisions (STAD) in the fourth grade students of SD Negeri 115 Pekanbaru. The issue of poor learning outcomes in teaching civics teacher caused not involve students in the learning process, the learning process tend to be boring, students just listening to the teacher, inactivity such as this will have an impact on student learning outcomes or achievement. The subject of this research is the fourth grade students of SDN 115 Pekanbaru. This research through four phases include planning, action, observation, and reflection. The data collection techniques in this research is through observation, testing, and documentation. Data analysis technique is to discuss the research results include the activities of teachers and students as well as student learning outcomes include, completeness individual, classical completeness, and calculate the percentage increase in student learning outcomes before and after the action. The results stated activity teachers and students increased during the learning process of type Student Team Achievement Divisions (STAD), so that the learning outcomes of students increased. Increased activity of teachers demonstrated by the observation of the first cycle assessment to obtain good categories, increased in the second cycle with very good category. Similarly, students activity, which in the first cycle to obtain the first meeting and the second meeting enough categories increased with good category, then increased in the second cycle reaches very good category. Improved learning outcomes in the first cycle of 13.1% to 71.1% classical completeness. At second cycle acquired learning outcomes increase of 24.7% with 93.3% classical completeness that is otherwise completed. This means that as expected the researcher. Thus we can conclude the implementation of cooperative learning model type STAD in class IV SDN 115 Pekanbaru can improve student learning outcomes of theCivics subjects (PKn).Keywords:Cooperative Learning Model Type STAD, PKnLearning Outcomes